THE INFLUENCE OF TRAINING METHODS AND AGILITY ON THE ABILITY TO DRIBBLE THE BALL IN SALFAS SOCCER SCHOOL ATHLETES - Yanuar, Adam Hafidh; Hartono, Mugiyo; Raharjo, Hermawan Pamot (Universitas Negeri Semarang, 2024)
The researcher's background is that dribbling the ball is still not good among athletes at the Salfas Soccer soccer school. The research problem is that the dribbling ability of Salfas Soccer soccer school athletes is still not good so it is still difficult to get past opponents. The aim of this research was to analyze the extent of training methods and agility on the ability to dribble the ball in Salfas Soccer soccer school athletes. This research uses an experimental method with a 2x2 factorial design. The population in this study were 60 athletes from the Salfas Soccer soccer school. The sample for this research was 48 athletes taken using a purposive sampling technique by setting certain criteria (agility). The instruments in this research used the Illinois Agility Test and a ball dribbling ability test. Data analysis in this study used the ANOVA (two-way) test. The results of this study show that 1) There is a significant difference in the influence of the ball feeling circuit training method with fixed ball feeling. 0.002 < 0.05. 2) There is a significant difference in the influence of high agility and low agility on ball dribbling ability 0.000 < 0.05. 3) There is an interaction between high agility trained using the ball feeling circuit training method and ball dribbling ability with results of 0.000 < 0.05. 4) There is an interaction between high agility trained using the fixed ball feeling training method and ball dribbling ability with results of 0.004 < 0.05. 5) There is an interaction between low agility trained using the ball feeling circuit training method and ball dribbling ability with results of 0.002 < 0.05. 6) There is an interaction between low agility trained using the fixed ball feeling training method and ball dribbling ability with results of 0.00 < 0.05. In conclusion, the circuit model ball feeling training method and fixed ball feeling model and high, low agility have a big influence on the ability to dribble the ball.